Privacy, Property and the Commodification of Our Identities - Prins, Corien (AHRC Research Centre for Studies in Intellectual Property and Technology Law, 2005)
Paper presented by Prins for the Privacy Workshop, chaired by Edwards and held in September 2005.
Keywords: Property; Privacy